Winter storms accelerate the demise of sea ice in the Atlantic sector of the Arctic Ocean - Graham, Robert M.; Itkin, Polona; Meyer, Amelie; Sundfjord, Arild; Spreen, Gunnar; Smedsrud, Lars H.; Liston, Glen E.; Cheng, Bin; Cohen, Lana; Divine, Dmitry; Fer, Ilker; Fransson, Agneta; et al. (Scientific Reports, 2019)
Published version, licensed by the CC BY 4.0 , available at http://dx.doi.org/10.1038/s41598-019-45574-5 A large retreat of sea-ice in the ‘stormy’ Atlantic Sector of the Arctic Ocean has become evident through a series of record minima for the winter maximum sea-ice extent since 2015. Results from the Norwegian young sea ICE (N-ICE2015) expedition, a five-month-long (Jan-Jun) drifting ice station in first and second year pack-ice north of Svalbard, showcase how sea-ice in this region is frequently affected by passing winter storms. Here we synthesise the interdisciplinary N-ICE2015 dataset, including independent observations of the atmosphere, snow, sea-ice, ocean, and ecosystem. We build upon recent results and illustrate the different mechanisms through which winter storms impact the coupled Arctic sea-ice system. These short-lived and episodic synoptic-scale events transport pulses of heat and moisture into the Arctic, which temporarily reduce radiative cooling and henceforth ice growth. Cumulative snowfall from each sequential storm deepens the snow pack and insulates the sea-ice, further inhibiting ice growth throughout the remaining winter season. Strong winds fracture the ice cover, enhance ocean-ice-atmosphere heat fluxes, and make the ice more susceptible to lateral melt. In conclusion, the legacy of Arctic winter storms for sea-ice and the ice-associated ecosystem in the Atlantic Sector lasts far beyond their short lifespan.